Algorithms and the grid - Fox, Geoffrey Charles; Aktas, Mehmet S; Aydin, Galip; Gadgil, Harshawardhan; Pallickara, Shrideep; Pierce, Marlon E; Sayar, Ahmet (My University, 2009)
We review the impact of Grid Computing and Web Services on scientific computing, stressing the importance of the “data-deluge” that is driven by deployment of new instruments, sensors and satellites. This implies the need to integrate the naturally distributed data sources with large simulation engines offering parallel low latency communication and so to integrate parallel and Grid computing paradigms. We start with an overview of these and the evolving service architectures. We illustrate the identified areas of interest for Algorithms and the Grid with the specific example of SERVOGrid that supports earthquake science research. We comment on the appropriate messaging infrastructure for Grids and data assimilation and contrast it with MPI.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Web services; Grid computing